Household Exposure to Severe Acute Respiratory Syndrome Coronavirus 2 and Association With Coronavirus Disease 2019 Severity: A Danish Nationwide Cohort Study. (23rd April 2021) - Broccia, Marcella; de Knegt, Victoria Elizabeth; Mills, Elisabeth Helen Anna; Møller, Amalie Lykkemark; Gnesin, Filip; Fischer, Thea K; Zylyftari, Nertila; Blomberg, Stig Nikolaj; Andersen, Mikkel Porsborg; Schou, Morten; Fosbøl, Emil; Kragholm, Kristian; et al.
Abstract: Background: Households are high-risk settings for the transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Severity of coronavirus disease 2019 (COVID-19) is likely associated with the infectious dose of SARS-CoV-2 exposure. We therefore aimed to assess the association between SARS-CoV-2 exposure within households and COVID-19 severity. Methods: We performed a Danish, nationwide, register-based, cohort study including laboratory-confirmed SARS-CoV-2–infected individuals from 22 February 2020 to 6 October 2020. Household exposure to SARS-CoV-2 was defined as having 1 individual test positive for SARS-CoV-2 within the household. Cox proportional hazards models were used to estimate the association between "critical COVID-19" within and between households with and without secondary cases. Results: From 15 063 multiperson households, 19 773 SARS-CoV-2–positive individuals were included; 11 632 were categorized as index cases without any secondary household cases; 3431 as index cases with secondary cases, that is, 22.8% of multiperson households; and 4710 as secondary cases. Critical COVID-19 occurred in 2.9% of index cases living with no secondary cases, 4.9% of index cases with secondary cases, and 1.3% of secondary cases. The adjusted hazard ratio for critical COVID-19 among index cases vs secondary cases within the same household was 2.50 (95% confidence interval [CI], 1.88–3.34), 2.27 (95% CI, 1.77–2.93) for index cases in households with no secondary cases vs secondary cases, and 1.1 (95% CI, .93–1.30) for index cases with secondary cases vs index cases without secondary cases. Conclusions: We found no increased hazard ratio of critical COVID-19 among household members of infected SARS-CoV-2 index cases. Abstract : Almost one quarter of multiperson households with a primary infection had secondary cases within the same household. We found no association between household transmission of severe acute respiratory syndrome coronavirus 2 and coronavirus disease 2019 severity.